FREQUENCY AND SUSCEPTIBILITY PROFILE OF PATHOGEN CAUSING URINARY TRACT INFECTION AT TERTIARY CARE HOSPITAL, PESHAWAR PAKISTAN - Tara, Tanveer; Ullah, Asad; Haq, Izhar Ul; Ullah, Naeem; Hassan, Muhammad; Umair, Muhammad (Annals of Allied Health Sciences, 2022)
Objective: To determine the prevalence and antibiotic resistance trend of urinary microbes obtained from urine samples of suspected hospitalized patients with urinary infections at a tertiary care hospital in Peshawar, Pakistan. Material & Methods: The current study was a cross-sectional study with an analysis of patients who were admitted for urinary tract infection (UTI) at the tertiary care hospital in Peshawar Pakistan. Results: A total of 145 participants were included and were selected among which 119 (82.1 %) infected patients were female, while 26 (17.9%) were male. UTI was most commonly seen in the age group of 20 to 60 years as 68.96% (100 cases) were reported). E.coli was the most frequently isolated organism with a frequency of 104 (71.8%) causing UTI. The Imipenem and fosfomycin was observed as most sensitive drug with 100% sensitivity for UTI, followed by penicillin, meropenem, nitrofurantoin, and gentamicin with a sensitivity of 94.7%, 89%, 82% and, 79.5% respectively. Conclusion: It is concluded that E. coli was the most common pathogen responsible for UTI followed by Staph. aureus, Klebsiella and Serratia. The Imipinem was observed as the most effective antibiotic against the common pathogens.